POSTMEMORY OF THE YOUTH OF THE COUNTRIES PARTICIPATING IN THE EURASIAN INTEGRATION: CURRENT STATE AND THE MECHANISMS OF FORMATION - Osadchaya, Galina; Vartanova, Marina; Kireev, Egor; Seleznev, Igor; Chernikova, Anna (Revista Inclusiones, 2020)
The article addresses the perception of the Soviet past image by the young generation of citizens of post-Soviet countries. A characteristic of the mechanisms of preservation and transfer of the information on the events of the 20th century and an assessment of the contribution of communication and symbolization to the formation of social memory are provided.